Taking the Complex Dynamics of Human–Environment–Technology Systems Seriously: A Case Study in Doctoral Education at the University of Luxembourg - König, Ariane; Ravetz, Jerome; Raber, Bo; Stankiewicz, Jacek; Rojas-Aedo, Ricardo; Hondrila, Kristina; Pickar, Karl (Frontiers in Sustainability, 2021)
Our existential sustainability challenges involve human-environment-technology systems that are complex, dynamic and tightly coupled. But at Universities, knowledge, in teaching and research, is mostly organized into discrete parcels, the disciplines. These are further divided into the categories of natural sciences, social science and the humanities. This paper addresses the question of how in their training of researchers, universities can equip them to better understand their roles and also to act as change agents. It describes a doctoral school course in transferable skills that is offered across faculties. The unique aim of the course is to provide a space for reflection on different research paradigms and the way they differ in their framing the role of a scientific researcher in pluralist societies that face existential challenges. The pedagogical framework and approach of the course encourages questioning one’s own ontological and epistemological assumptions about the constitution of our world and how we might better understand it in dialogues with participants who come from diverse disciplinary backgrounds. The course includes discussions of: what is a discipline, and how disciplines differ in their understandings of the world and of the role of science within it; how tools and representations can shape or breach disciplinary paradigms; how instrumental science and interdisciplinarity can raise the dilemma of rigor or relevance; how complexity, contradictions and values are embraced in responsible research design, and last but not least we discuss the relation of science, progress and open futures. The course introduces diverse more recent approaches to scientific inquiry that harness the potential of democratizing science in our networked knowledge society, including critical interdisciplinarity, post-normal science, citizen science and transformative sustainability science, that complement normal disciplinary research practices.